Análisis de la conducta del hematocrito en perros tratados con Autohemoterapia - Díaz Robles, Stefany Cisney (2023)
The present document below consists of an experimental study to analyze the behavior of hematocrit in dogs treated with Autohemotherapy (AHT) also known as immunotherapy, serum therapy or autotransfusion is a widely used method, some studies carried out denote that it is a therapeutic technique in that presents satisfactory clinical results to treat various pathologies, making it a promising therapy. The procedure consists of collecting a whole blood sample from the sick or healthy animal, which is immediately administered intramuscularly, subcutaneously, intravenously or intradermally. For this procedure, field work was carried out at the "Hospivet" Babahoyo Veterinary Hospital where samples were taken. blood samples from 10 dogs from which 5 of them had 5ml extracted and 3ml of autologous blood was extracted from the other 5 patients to then be inoculated intramuscularly, this process was carried out for five weeks at intervals of seven days after each session of therapy, a blood sample was extracted from each patient to be analyzed and processed in the laboratory, the results obtained show values that the application of a 3ml dose in 5 patients significantly increased the hematocrit values, unlike the 5ml dose in the during the five weeks of treatment.